2017
DOI: 10.1002/dmrr.2887
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes as a risk factor for acute coronary syndrome in women compared with men: a meta‐analysis, including 10 856 279 individuals and 106 703 acute coronary syndrome events

Abstract: The excess risk of ACS associated with diabetes is significantly higher in women than in men. This finding may be explained by more adverse cardiovascular risk profiles and suggests that further work is needed to clarify the relevant biological, behavioural, and social mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 87 publications
(171 reference statements)
4
22
0
1
Order By: Relevance
“…Individuals with T2DM have a 2 to 3-fold greater risk of CVD than people without T2DM, with women showing an increased elevated risk compared to men (2.5 fold risk increase in women compared to 1.7-fold in men) (41). Moreover, people with T2DM have an increased risk of long-term mortality following coronary revascularization in both stable ischemic and ACS populations (4246).…”
Section: Resultsmentioning
confidence: 99%
“…Individuals with T2DM have a 2 to 3-fold greater risk of CVD than people without T2DM, with women showing an increased elevated risk compared to men (2.5 fold risk increase in women compared to 1.7-fold in men) (41). Moreover, people with T2DM have an increased risk of long-term mortality following coronary revascularization in both stable ischemic and ACS populations (4246).…”
Section: Resultsmentioning
confidence: 99%
“…Diet quality is important for individuals with diabetes mellitus. The American Diabetes Association recommends “healthful eating patterns, emphasizing a variety of nutrient-dense foods” to help “attain individual glycemic, blood pressure, and lipid goals” and to “delay or prevent the complication of diabetes.” [1] With regard to complications of diabetes, and in particular cardiovascular disease (CVD) outcomes, which are more common in those with diabetes [2, 3], emerging data underscore the importance of dietary pattern for those with diabetes. In observational studies focusing on participants with diabetes at baseline, a higher quality diet was associated with decreased rates of CVD events and CVD mortality [4] and total mortality [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that coronary atherosclerotic plaque rupture, vasospasm and consequent platelet adhesion, aggregation, and secondary thrombosis are the main pathophysiological mechanisms of ACS [10, 11]. Additionally, diabetes [12], hypertension [13], obesity [14], smoking [15], and older age [16] are risk factors that promote the development and progression of ACS. A large number of studies have indicated that inflammatory factors are also closely related to ACS.…”
Section: Introductionmentioning
confidence: 99%